Air pollution in Reykjavík and use of drugs for obstructive airway diseases - Krage Carlsen, Hanne, 1981- (2010)
Ritgerðin er lokuð til janúar 2012 vegna birtingar í ritrýndu tímariti Introduction: Iceland's capital region has overall good air quality, but sulphur gas (H2S) emissions from geothermal power plants and particle pollution (PM) are of concern. Short¬ term effects of ambient H2S at moderate levels are largely unknown. PM is known to aggravate symptoms of respiratory disease. This is the first study to examine the association between daily air pollution levels and respiratory health in Iceland's capital area. Data: A timeline of the daily number of adults in the capital area who were dispensed one or more drugs for obstructive pulmonary diseases (WHO ATC category R03) were obtained from by the Directorate of Health drug registry. Data on PM10, NO2, O3 and H2S as well as weather factor measurements were provided by the City of Reykjavík Environmental Office. The study period was from February 22nd 2006 to September 30th 2008. Methods: The daily number of individuals dispensed drugs for obstructive pulmonary disease was modeled as a function of three-day moving average¬ and the three-day moving average of the daily maximum 1¬hour mean (peak pollution) of the pollutants with lag 0 to 14 days using Poisson regression. The model included covariates to adjust for climate, time trends, influenza season and day¬ of week. Insignificant covariates were excluded from the model. Results: There was a positive association between air pollution levels and the daily number of individuals who were dispensed drugs with a lag of three days. The association was significant (p < 0.05) for lag 3 to 5 of the 24¬hour mean of H2S and PM10 in a three-day moving average model. The increase corresponds to an increase in the number of individuals who were dispensed drugs of 3% and 2% between the 10th and 90th percentile of PM10 and H2S respectively. Risk estimates for the number of individuals dispensed drugs as a function of peak pollution were similar to estimates for three-day moving average for PM10 and H2S, 6% and 5% for NO2 and ...